AI in higher education: a systematic literature review - Castillo-Martínez, Isolda Margarita; Flores-Bueno, Daniel; Gómez-Puente, Sonia M.; Vite-León, Victor O. (Frontiers in Education, 2024)
The increasing reliance on technology within higher education necessitates a thorough examination of artificial intelligence's (AI) application in academic research. This analysis aims to elucidate both the advantages and challenges associated with AI utilization, thereby paving the way for future inquiries. Such studies will be instrumental in delineating strategies for the effective integration of AI tools in scholarly research, ensuring their optimal use in advancing the field.Objective: The purpose of this research is to identify the benefits and challenges of the use of AI in the field of scientific research by analysing experiences that have implemented AI in scientific research carried out at the university level through a systematic literature review.The research questions that guided the systematic literature review were as follows:(1) What are the benefits of using AI in research? (2) What are the challenges of using AI in research?(3) What are the use and benefits of AI in scientific writing including limitations? (4) What are the main lines of research identified in studies that address scientific practice with artificial intelligence in the university context? The articles analysed were published in 2023.After applying the inclusion and exclusion criteria, 85 articles were analysed. The analysis allowed findings such as the usefulness of ChatGPT in different disciplinary areas, challenges such as being able to identify artificial intelligence resources limitations and benefits such as being able to make processes of different kinds more efficient.It was possible to establish that although the studies analysed identified advantages in the application of AI in scientific research, it was also detected that it is necessary to have a critical and creative look to make use of AI resources, such as ChatGPT, in order to use them only as support tools and thus be able to take care of the rigor and quality in the elaboration of scientific texts.